A Qualitative Inquiry into Central American Immigrant Women’s Perceptions of Adult learning - Ana Guisela Chupina (Adult Education Research Conference, 2004)
Five Central American immigrant women living in a metropolitan area of the Midwestern United States were interviewed. Findings revealed that adult learning was perceived as empowering and experienced as continuous, informal, experiential, and relational